The Roles of Strategic Planning in Organizational Crisis Management: The Case of Jordanian Banking Sector - Hasan Yousef Aljuhmani; Okechukwu Lawrence Emeagwali (International Review of Management and Marketing, 2017)
This study aimed to identify the roles of strategic planning in organizational crisis management on Jordanian banks in Ramtha. The main goal of conducting this study is to measure the external and internal orientation in strategic planning and the crisis management from four different perspectives: signal detection, preparation and prevention, crisis recovery and learning on Jordanian banks in Ramtha. The research provides a substantial and original contribution to the fact that it deals with economic sector, the banking sector, which is one of the most vulnerable sectors of the crises, especially in the light of the political conditions, economic instability and the Arab Spring, which is pushing the researcher to know how to take benefit of the features provided by strategic planning and its role in crisis management. This study also showed that employees were either ignorant about crisis management stages or there was a clear disregard for crisis management stages at Jordanian banks in Ramtha.